Identification of volatile secondary metabolites from an endophytic microfungus Aspergillus nomius KUB105 [Pengenalpastian Metabolit Sekunder Meruap daripada Kulat Mikro Endofitik Aspergillus nomius KUB105] - Lateef Adebola Azeez; Sepiah Muid; Bolhassan Mohamad Hasnul (Malaysian Society of Analytical Sciences, 2016)
Microfungi are a highly diverse group of micro-organisms and important components of the ecosystem with great potential for diverse metabolite production. During a survey of microfungi on leaves in a National Park in Sarawak, an uncommon endophytic microfungus Aspergillus nomius was encountered. The metabolite production of this microfungus was investigated by growing it in a liquid basal medium for 2 weeks. Gas Chromatography - Mass Spectrometry (GC-MS) and Fourier Transform Infrared (FTIR) profiling of the secondary metabolites produced by this microfungus in the liquid medium revealed the presence of 46 different secondary metabolites. The metabolites include saturated hydrocarbons, alkyl halides, alcohols and an unsaturated hydrocarbon. Majority of the metabolites produced were saturated hydrocarbons. Tetracosane, Icosane and 10-Methylicosane were the most abundant metabolites identified while heptadecane and 2,4-dimethylundecane were the least abundant respectively. This study is the first GC-MS and FTIR report of secondary metabolites from A. nomius. The results from this study confirm the ability of microfungi to produce diverse metabolites, including saturated hydrocarbons